Peran Tax Amnesty sebagai Pemoderasi pada Sanksi Perpajakan dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak (Studi Empiris pada UMKM Kota Semarang) - Irvan Agy Pranandika; Jaeni Jaeni (Universitas Batanghari Jambi, 2023)
The purpose of this study is to analyze the role of tax amnesty as a moderator of tax sanctions and taxpayer awareness of the compliance of UMKM taxpayers in the city of Semarang. The variables used are tax sanctions and taxpayer awareness as independent variables, while tax compliance is the dependent variable and tax amnesty is the moderating variable. In this study, a questionnaire was used which was distributed to MSME taxpayers with an annual turnover of <4.8 billion in the city of Semarang, with incidental sampling. The population in this study is MSME taxpayers in Semarang using a sample of 122 MSME respondents. The results of this study indicate that tax sanctions, taxpayer awareness and tax amnesty have a positive and significant effect on MSME taxpayer compliance. While the tax amnesty does not moderate tax sanctions, taxpayer awareness of MSME taxpayer compliance.